Numerical Simulation of Heat Transfer in a Closed Two-Phase Thermosiphon; Key Engineering Materials; Vol. 743 : High Technology: Research and Applications (HTRA 2016) - Arkhipov V. Vladimir (2017, 2017)
Title screen